EFFECTS OF USE OF STANDARD RECIPE ON FOOD QUALITY CONTROL IN SELECTED FAST FOOD OUTFITS IN LAGOS STATE - BAKARE , K. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Recently, the idea of eating away from home has become the order of the day as a result of light economic activities in the era of industrialization cum capitalization. The paper examined the function of standard recipe in food quality control in fast food. The results revealed that standard recipe is significant to quality control in fast food. The findings further showed that effective application of standard recipe in fast food operation required staff induction programme (?2 = 9.14, p<0.05). Also the results indicated that use of standard recipe waste time (?2 =6.17, p<0.05). The use of standard recipe was also found to have significant relationship with trademark creation (?2 =8.14, p<0.05), taste consistency (?2 = 4.17, p<0.05), cooking moderation (?2 = 5.65, p<0.05). It was concluded that majority of fast foods use standard recipe in varying degrees, and standard recipe was found to have significant relationship with quality control. The study recommended that consumer protection agencies should expedite action on enforcement of the use of standard recipe in all food operations of fast foods. They should also constitute a board that will see to the training/induction of staff on the rudiments of standard recipe for effective and efficient application.